2022
DOI: 10.17770/eid2022.1.6806
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of Autogenous Training Techniques for Psychological Preparedness of Sports School Students

Abstract: Athletes' success in sports is linked not only to good physical, technical and tactical preparedness, but also to psychological fitness. In sports psychology there are two basic types of psychological preparation, namely general psychological preparation and special psychological preparation. Just as comprehensive physical preparation is the basis for an athlete's special, technical, tactical fitness, so comprehensive psychological preparation is the basis for an athlete's mental toughness both during the trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…This study's results align with previous research (Vecenane & Vazne, 2022). They conducted a study on 220 college students and concluded that those who engage in regular physical activity have better levels of physical fitness and reduced levels of mental stress compared to their peers who do not exercise.…”
Section: Discussionsupporting
confidence: 88%
“…This study's results align with previous research (Vecenane & Vazne, 2022). They conducted a study on 220 college students and concluded that those who engage in regular physical activity have better levels of physical fitness and reduced levels of mental stress compared to their peers who do not exercise.…”
Section: Discussionsupporting
confidence: 88%
“…They also agree that the training aims to help athletes improve their skills and achieve maximum achievement. Vecenāne and Vazne (2022) state that training is a crucial part of preparing athletes for sports competitions. In addition, Wachowicz (2019), defines training as one of the means in preparing athletes to achieve the best conditions.…”
Section: Resultsmentioning
confidence: 99%